ANALISIS FAKTOR PENYEBAB TINGGINYA TINGKAT GOLPUT MASYARAKAT PADA PEMILUKADA KABUPATEN BUNGO TAHUN 2011 DI KECAMATAN PASAR MUARA BUNGO - Harpinsyah Harpinsyah; Halim Perdana Kusuma (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
This research was conducted at Pasar Muara Bungo District. The location was chosen on purpose or "purposive". The location was chosen because it was included in 3 (three) Districts that had a high level of golput (white group) compared to other Districts in Bungo Regency, namely 4.817 voters or 10,5%. This study aims to analyze the factors that influence the high level of abstention from the community in the 2011 Pemilukada Bungo Regency in Pasar Muara Bungo District. The method in this research is quantitative with data taken from the Permanent Voters List (DPT) of the Bungo Regency Pemilukada in 2011. The results show that among the factors that cause low levels of community participation in post-conflict local elections are socio-economic factors, passive community participation and psychological and rational factors